Pre-service Teachers Perspectives on English Coursebook for Senior High Schools in Indonesia - Jemadi, Fransiskus; Juita Ekalia, Yulian; Par, Leonardus; Nabung, Adrianus (Universitas Nusantara PGRI Kediri, 2024)
A textbook is an inseparable part of the teaching and learning process. This research was aimed at discovering pre-service teachers’ perception of the ELT textbook, Buku Bahasa Inggris for Students grade XI. This qualitative study involved 18 pre-service teachers who were doing their teaching practicum in different senior high schools in Manggarai, East Nusa Tenggara Province. They were chosen purposefully by the researchers and voluntarily engaged in semi-structured interviews to discover their perspectives on the English textbook they used during their teaching practicum. The results showed that they had mixed opinions about their textbooks, ranging from positive to negative, depending on various factors such as their learning objectives, preferences, expectations, and experiences. The observations and conclusions from this study may be useful for educators and coursebook designers in developing English coursebooks that can improve students' motivation, engagement and language learning outcomes.